102 PHEOCHROMOCYTOMA IN A PATIENT WITH NEUROFIBROMATOSIS 1 PRESENTING WITH AN ACUTE MYOCARDIAL INFARCTION. (1st January 2005) - Boulkina, L.; Ahmed, S.; Vellappan, P.; Drake, A.; Tanenberg, R.
Abstract : A 43 year old female presented with chest pain and shortness of breath and was determined to have hypertensive crisis, pulmonary edema, and acute non-ST elevation myocardial infarction (MI). She had a history of neurofibromatosis 1 (NF1), poorly controlled hypertension (HTN) and spells of headaches, palpitations and sweating. On transthoracic echocardiogram she had a hyperdynamic left ventricular function with ejection fraction of 75% and inferior and inferoseptal wall motion abnormality. Cardiac catheterization revealed a nonobstructive coronary artery disease. Given her NF1, HTN and the presence of the "classic triad" of pheochromocytoma, she was screened for this tumor. Plasma catecholamine metabolites levels drawn on the third day post acute MI with the patient pain free and stable evidenced a 10-fold increase of free normetanephrine and 4.5-fold increase of free metanephrine. MRI of adrenal glands revealed a 4.5 × 3.3 cm right adrenal mass. The patient was diagnosed with pheochromocytoma and started on labetalol. The patient underwent uncomplicated laparoscopic adrenal pheochromocytoma excision two weeks after the first admission. Pathology has confirmed the diagnosis of pheochromocytoma. Conclusion: Adrenergic crisis secondary to pheochromocytoma can result in acute MI even in the absence of the obstructive coronary artery disease. Consider pheochromocytoma early in the management of unexplained hypertension and MI in patients with NF1.